2022
DOI: 10.1080/00480169.2022.2139306
|View full text |Cite
|
Sign up to set email alerts
|

Use of equine chorionic gonadotropin in lactating dairy cattle: a rapid review

Abstract: Supplementary Information 1. Search strategies. Web of Science search termsALL=("pregnant mare serum gonadotropin" OR "pmsg" OR ecg OR "equine chorionic gonadotropin") AND ALL=( "oestr* synchroni*ation" OR "estr* synchroni*ation" OR "timed artificial insemination" OR ovsynch OR anestr* OR anoestr* OR treat* OR "fixed time artificial insemination" OR "fixed time AI" OR ftai OR synch* OR "no visible oestr*" OR "no visible estr*" OR nvo OR ndo OR "no detected oestr*" OR "artificial inseminat*" OR ai OR mat* ) AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The hormonal stimulating folliculogenesis is most developed in pig and cattle breeding (Cunha & Martins, 2022;Beasley et al, 2023). Most of those industries apply methods in rabbit breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The hormonal stimulating folliculogenesis is most developed in pig and cattle breeding (Cunha & Martins, 2022;Beasley et al, 2023). Most of those industries apply methods in rabbit breeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have indicated that good fertility owing to eCG treatment is limited in lactating dairy cows. Recently, Beasley et al summarized in a rapid review that the efficacy of eCG in improving the reproductive performance of lactating cows has been inconsistent [18]. Garcia-Ispierto et al reported that eCG treatment of dairy cows without signs of estrus could improve fertility [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Beasley et al . summarized in a rapid review that the efficacy of eCG in improving the reproductive performance of lactating cows has been inconsistent [ 18 ]. Garcia-Ispierto et al .…”
mentioning
confidence: 99%